2019
DOI: 10.1021/acsnano.9b03419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control of Charge Density Wave Order in Monolayer 2H-TaS2

Abstract: For quasi-freestanding 2H-TaS 2 in monolayer thickness grown by in situ molecular beam epitaxy on graphene on Ir(111), we find unambiguous evidence for a charge density wave close to a 3 × 3 periodicity. Using scanning tunneling spectroscopy, we determine the magnitude of the partial charge density wave gap. Angle-resolved photoemission spectroscopy, complemented by scanning tunneling spectroscopy for the unoccupied states, makes a tight-binding fit for the band structure of the TaS 2 monolayer possible. As hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 60 publications
7
67
2
Order By: Relevance
“…4. In line with former theoretical results [66] and experiments [62] we find that electron doping pushes the wave vector of the leading lattice instability towards the M point. Hole doping of µ = −119 meV on the other hand shifts the instabilities further away from M and also lets additional "fragile" instabilities between Γ and K emerge, which depend very sensitively on the thermal broadening k B T of the electronic Fermi distribution function.…”
Section: B Doping Dependence and Van Hove Scenariossupporting
confidence: 92%
See 1 more Smart Citation
“…4. In line with former theoretical results [66] and experiments [62] we find that electron doping pushes the wave vector of the leading lattice instability towards the M point. Hole doping of µ = −119 meV on the other hand shifts the instabilities further away from M and also lets additional "fragile" instabilities between Γ and K emerge, which depend very sensitively on the thermal broadening k B T of the electronic Fermi distribution function.…”
Section: B Doping Dependence and Van Hove Scenariossupporting
confidence: 92%
“…Charge doping is known to affect CDW instabilities by shifting the ordering wave vectors and suppressing or supporting CDW order in many materials from high-T c superconductors [4] to TMDCs [44,[81][82][83][84] and 1H-TaS 2 in particular [62,66,85,86]. We studied the dependence of the LA phonon mode on charge doping in the phonon self-energy formalism [Eqs.…”
Section: B Doping Dependence and Van Hove Scenariosmentioning
confidence: 99%
“…For monolayer TaSe 2 , due to its extended charge distribution, charge transfer tends to accumulate between TaSe 2 and graphene, so that the intralayer covalency is reduced; CDW is therefore enhanced. Interestingly, CDWs were found to be absent in epitaxial monolayer TaS 2 on Au(111) substrate 37 , but persist in MBEgrown monolayer TaS 2 on graphene/Ir(111) 38 as well as in the exfoliated monolayer studied here. These findings provide further evidence that the CDW formation in such atomically thin TMDs is, in general, highly susceptible to the surrounding environment, which could be a neighboring layer or even a substrate.…”
Section: Discussionmentioning
confidence: 66%
“…Meanwhile, the trigonal symmetry of Au(111) substrate enforces the original symmetry of pristine monolayer TaS 2 , thereby avoiding any lattice deformation. Of course, hybridization between monolayer TaS 2 and the Au(111) substrate could significantly affect its electronic band structure [38][39][40] , and correspondingly, its intrinsic properties. Alternatively, when the substrate is made of chemically inactive orbitals (such as p π states in graphene), the CDW is still inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…FFT, fast Fourier transform; TEM, transmission electron microscope concentration ( Figure 5F). 100 Calculations showed that charge doping from Li atoms disturbed phonon dispersions, which changed CDW structures ( Figure 5G).…”
Section: Correlated Statesmentioning
confidence: 99%